Primary School Children with Special Education Needs - Gavrilushkina O.P.; Egorova M.A. (Psihologiceskaâ nauka i obrazovanie (2007), 2016)
The paper analyses the modern situation of development in elementary school children. As it is shown, children with special educational needs display a delay in social maturation. According to the outcomes of a longitudinal study on behaviour in communicative/activity situations in normally developing children and children with disabilities, at the point of school entry the following features are prominent: incomplete decentration process; low levels of verbal regulation of actions; underdeveloped dialogue functions (communicative, programming, controlling/regulative); decrease in self-regulation, programming and control; lack of position dynamics in partnership etc. The paper also provides a review of the new basic professional education programme in “Correctional and Developmental Work with Children” designed in modules and based on networking. It is argued that students graduating in this programme have mastered all competencies required for working with children with special needs.